(untitled) (Romanian Studies Today, 2024)
Through the present paper, we aim to analyse and describe at the same time the paradigmatic relationship of semantic equivalence within the terminology of atmospheric phenomena in the Romanian language, starting from the descriptive theories of Coșeriu (2000, 2002) and Bidu-Vrănceanu (1984, 2005, 2008). The study includes the componential, semantic and morphological analysis of a wide inventory of terms, starting from the work Dicționarul fenomenelor atmosferice (Florescu ed., 2015). In order to follow the purpose of this study, the terms were divided according to the typology of the equivalence relation in which they fall and according to the way the terms are formed. We emphasize the fact that in our analysis we used the functional categorization already displayed in DFA by language registers (scientific and popular).